Hubungan Fungsi Manajemen Kepala Ruang dengan Motivasi Perawat dalam Melakukan Discharge Planning - Tazkia Rahman; Endang Pertiwiwati; Herry Setiawan; Herry Setiawan (Poltekkes Kemenkes Bengkulu, 2020)
The function head of the room is a first line nursing manager who has the functions of planning, organizing, directing and supervising. Motivation is a problem for nurses in achieving and improving the quality of nursing services, especially on discharge planning. The phenomenon found in RS Kota X was the function of the head of the room management has not been carried out to the maximum and the motivation of the implementing nurse in discharge planning is still not optimal. The purpose of this research is to analyze the relationship between management function of the head of the room with motivation of nurses in discharge planning at RS Kota X. The study design was cross sectional with proportional stratified random sampling and data collectionntechniques carried out on 92 respondent nurses in RS Kota X from September 13, 2018 till February 28, 2019. The research instrument used a management function and motivation of nurses in discharge planning questionnaire. The results of the study was 60.9% poor and the motivation of nurses in discharge planning was 67,4% moderate. The relationship between the management function of the head of the room with the motivation of nurses in carrying out discharge planning in RS Kota X with a p value of 0.009 <0.05.The function of good head of the room management can increase motivation in discharge planning.